Best nursing practices in diabetes education for the hospitalized child: an integrative review - Luíza de Oliveira Messias Ortiz; Elaine Buchhorn Cintra Damião; Lisabelle Mariano Rossato; Roberta Cristiane Pascarelli Alves (Universidade Federal de Goias, 2017)
The incidence of Diabetes Mellitus type 1 (DM1) has increased in the last years, with a consequent growth of child hospitalizations due to diabetic prime decompensation, with growing need of an educational process. Thus, our objective was to identify in the literature the best nursing practices in diabetes education for hospitalized children with DM1 and their families. We conducted an integrative review with the descriptors: Diabetic Ketoacidosis, Diabetes Education, Nursing and Child, Hospitalized, and the free search in reference journals and similar articles. We selected four studies, and we identified three categories: Family Involvement and Empowerment in the Diabetes Educational Process; Performance of the Multi-professional Team; Definition and Content of the Educational Process. We concluded that the educational process should include the family, it should be conducted by a multi-professional team and based on scientific evidence. We identified few studies, showing the need for more studies in the field.